Biochemistry : The Chemical Reactions of Living Cells Ed 2 - David E Metzler (New Delhi Elsevier, 2006)
Biochemistry: The Chemical Reactions of Living Cells is a well-integrated, up-to-date reference for basic biochemistry, associated chemistry, and underlying biological phenomena. Biochemistry is a comprehensive account of the chemical basis of life, describing the amazingly complex structures of the compounds that make up cells, the forces that hold them together, and the chemical reactions that allow for recognition, signaling, and movement. This book contains information on the human body, its genome, and the action of muscles, eyes, and the brain.
Keywords: Biochemistry